TRANSFORMATIONAL LEADERSHIP, ORGANIZATIONAL CULTURE, AND EMPLOYEE PERFORMANCE: THE MEDIATING ROLE OF JOB SATISFACTION IN PUBLIC SECTOR ORGANIZATIONS - Safril Gazali (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
This study examines the direct and indirect effects of transformational leadership and organizational culture on employee performance in a public sector context, with job satisfaction as a mediator. Employing a quantitative survey design and structural equation modeling (SEM), data were collected from public servants at the Regional Secretariat of Tanah Datar Regency, Indonesia (N = 121). Results indicate that transformational leadership and organizational culture both positively and significantly influence performance. Moreover, job satisfaction significantly mediates these relationships, with indirect effects observed. These findings contribute to leadership and organizational behavior theory by elucidating psychological mechanisms underlying performance in public institutions and offering practical implications for public HR management.